A Novel Laser Energy Ablation Catheter for Endocardial Cavo-Tricuspid Isthmus Ablation and Epicardial Ventricular Lesion Formation: An in vivo Proof-of-Concept Study - Krist, Dennis; Linz, Dominik; Schotten, Ulrich; Zeemering, Stef; Leenen, Dwayne (Frontiers in Medical Technology, 2022)
Aim: This proof-of-concept study aimed to investigate atrial and ventricular lesion formation by a 20mm linear laser ablation catheter, regarding lesion depth and tissue damage. Methods: Six female swines underwent standard femoral vein access to intro-duce a novel 20mm linear laser ablation catheter in the right atrium to perform endocardial cavo-tricuspid isthmus (CTI) ablations. The navigation took place under fluoroscopy with additional visualization by intracardiac echocardio-graph. Epicardial ablations were performed on the surface of the left ventricle (LV), right ventricle (RV) and right atrial appendage (RAA) via a sternotomy. Procedural safety was assessed by registration of intraprocedural adverse events and by macroscopic examination of the excised hearts, for presence of charring or tissue disruption at the lesion site. Results: Altogether 39 lesions were created, including eight endocardial CTI (mean lesion length 20.6±1.65mm), 26 epicardial ventricle (mean lesion length LV: 25.3±1.35mm, RV: 24.9±2.40mm) and five epicardial appendage ablations (mean lesion length RAA: 26.0±3.16mm). Transmurality was achieved in all CTI and atrial appendage ablations, in 62% of the RV ablations and in none of the LV ablations. No perforation or steam pop occurred, and no animal died during the procedure. Conclusion: In this porcine study, the 20mm linear laser ablation catheter has shown excellent results for endocardial cavo-tricuspid isthmus ablation and resulted in acceptable lesion depth during atrial and ventricular epicardial abla-tion. The absence of tissue charring, steam pops, or microbubbles under the experimental conditions, suggests a high degree of procedural safety.